Public Policy toward Nongovernmental Organizations in Developing Countries - Jack, William (World Bank, Washington, DC, 2014)
The author presents two descriptive models of nongovernmental organizations and poses mormative questions about public polcy toward nongovernmental organizations (NGOs). In situations in which optimal government intervention in a distorted or inequitable economy employs an NGO-like body, he considers which kinds of NGO might be used. First, in many developing countries NGOs participate in the delivery of what are essentially private goods--in particular, health care and education. In an economy without NGOs, there may be good redistributive and efficiency reasons for the government to provide these goods in kind. But if direct government provision of such services is ineffective or inefficient, when is contracting out to an NGO-like institution preferable to using a traditional for-profit firm? (Another way to frame this is to ask: What is the optimal taxation and regulation of private providers of publicly financed services?) NGOs also provide useful real and financial links with external donors. They are used to provide services the government favors and donors are willing to fund. In this model, the service provider is chosen to yield the best outcome for both government and donor. In this context, the author compares an international NGO and a grassroots organization. It may be more efficient to transfer donor funds through an international NGO than through a local NGO, but when donor-government cooperation fails, a project implemented by an international NGO is effectively killed. If a project implemented by a local organization can limp along, this otherwise less efficient organization might be preferred.